Moderasi Hubungan Financial Literacy dengan Keputusan Investasi terhadap Peran Herding Behavior bagi Investor Pemula - Saputra, Syailendra Eka; Natassia, Rizky; Utami, Hayu Yolanda (Jurnal Informatika Ekonomi Bisnis, 2022)
The role of herding behavior (HD) is very much needed in moderation to support Investment Decisions (IC) for novice investors. This study aims to measure the size of Financial Literacy (FL) in making the right decisions. The data processed in this study are 158 novice investor respondents who invest in stock-type securities in Indonesia. The sampling method was carried out randomly (probability sampling) which was collected through the Google form. The data analysis method used is to answer the truth of the hypothesis using the help of the Structural Equation Model (SEM). The results of hypothesis testing found that FL had a positive and significant effect on KI and HD. The magnitude of the influence value is less than 0.05. The same test model for HD also has a positive effect on KI with a value smaller than 0.05. The test value of this effect on HD is not a direct effect, with a coefficient value of -0.039 which is smaller than 0.05. The conclusion of this study is that HD does not moderate the relationship between FL and KI for novice investors who invest in stock-type securities in Indonesia. So that this research can be used as a reference in making decisions for novice investors.